2021
DOI: 10.1128/spectrum.00262-21
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Genetic Markers for Antimicrobial Resistance in Mycoplasma bovis

Abstract: Mycoplasma bovis is a leading cause of pneumonia but also causes other clinical signs in cattle. Since no effective vaccine is available, current M. bovis outbreak treatment relies primarily on the use of antimicrobials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…A G748A mutation in both 23S rRNA alleles, as well as a Gln93His mutation in the rplv gene were found. In previous studies, G748A mutations have been observed in isolates resistant to tylosin and tilmicosin, whereas the Gln93His mutation has been linked to resistance against macrolides (gamithromycin and tylosin) when combined with a mutation in domain 5 of 1 or both 23S rRNA gene alleles on position A2058 36‐39 . In this case, no mutations on position A2058 were found.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…A G748A mutation in both 23S rRNA alleles, as well as a Gln93His mutation in the rplv gene were found. In previous studies, G748A mutations have been observed in isolates resistant to tylosin and tilmicosin, whereas the Gln93His mutation has been linked to resistance against macrolides (gamithromycin and tylosin) when combined with a mutation in domain 5 of 1 or both 23S rRNA gene alleles on position A2058 36‐39 . In this case, no mutations on position A2058 were found.…”
Section: Resultsmentioning
confidence: 59%
“…In previous studies, G748A mutations have been observed in isolates resistant to tylosin and tilmicosin, whereas the Gln93His mutation has been linked to resistance against macrolides (gamithromycin and tylosin) when combined with a mutation in domain 5 of 1 or both 23S rRNA gene alleles on position A2058. [36][37][38][39] In this case, no mutations on position A2058 were found. Additionally, 1 new Lys184Asn mutation was found in the rpId gene.…”
Section: Laboratory Diagnosismentioning
confidence: 59%
“…The significant NVs linked to TIL resistance were primarily ABC transporters, giving credence to the idea of innate resistance through efflux pumps. Bokma et al also reported multiple ABC-type macrolide efflux pump genes [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only a few GWAS studies have been conducted to characterize AMR in M. bovis [ 26 , 27 ], which may be related to the technical expertise required in conducting such studies. Furthermore, a limitation of GWAS is the occurrence of false positive associations between the traits and genetic variants, commonly referred to as “ p -value inflation” [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation